NIKAH BAWAH TANGAN ATAS TUDUHAN ZINA (QADHAF) PERSPEKTIF SOSIOLOGI HUKUM DI KECAMATAN RASANA’E BARAT - Syarif Hidayatullah (Fakultas Syariah IAI Muhammadiyah Bima, 2018)
Polemics regarding the lives of men and women were not only the matter of marriage and divorce, but also zina (fornication), which often causes problems in the community. This study explored the perspective of Bimaness regarding the concept of zina; and whether research anchored in the sociology of law gathered the data and empirical evidence in the field analyzed using phenomenological dan fungsional structural approaches. The empirical findings showed that, first, Bimanese community, as in Islam, regarded zina as cruel acts. Therefore, sanction was imposed on the fornicators to uphold ‘amarma’rufnahimungkar’ (enjoining good and forbidding wrong’ principle); second, the sanction imposed on the fornicators was somehow unregistered marriage. The sanction imposed was deemed to be a panacea for some people, while others regarded it as merely no more than just a sanction. For the former, such a sanction could generate deterrent effects: the perpetrator were ashamed of the society and family regarding their immoral acts and were compelled to be responsible. The reason for the latter to regard the sanction as a mere sanction was due to the illegal marriage status, an unregistered marriage pertaining to the state law. Thus, the marriage would not last longer, and the public could only impose, yet did not escort sanction.